The Practice of Al-Qardh bi Syarth al-Bay’ in Farmers Financing: A Fiqh Muamalah Analysis - Fifi Faradila Safitri.M; Sulyman Muhammad-Busyari; Hasniati (Fakultas Syariah IAIN Kendari, 2026)
The development of community economic practices shows the emergence of various hybrid contracts as a response to socio-economic needs, one of which is al-qardh bi syarth al-bay’, a loan contract accompanied by a condition of a sale transaction. Although studies on Islamic financing in the agricultural sector have grown significantly, most research focuses on formal financing institutions, while informal financing practices between farmers and collectors remain relatively underexplored in the perspective of fiqh muamalah. This study aims to analyze the mechanism of al-qardh bi syarth al-bay’ in rice harvest financing and examine its compliance with Islamic commercial law principles. The research employs a qualitative approach with an empirical juridical method through a case study in Bumi Raya Village, Andoolo District, Konawe Selatan Regency. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using descriptive qualitative analysis. The findings show that farmers receive cash loans with the condition that their harvest must be sold to the lender at a price predetermined at the beginning of the agreement. Empirically, this practice functions as an informal financing mechanism that helps farmers obtain capital amid limited access to formal financial institutions. However, from the perspective of fiqh muamalah, the practice potentially contains elements of riba, as lenders gain benefits through purchasing harvests below market prices and create unequal bargaining power between farmers and collectors. This study recommends the development of more equitable and transparent Islamic agricultural financing models through Islamic microfinance institutions or sharia cooperatives. Keywords: Agricultural Financing; Al-Qardh bi Syarth al-Bay’; Fiqh Muamalah.